"THE PREVALENCE OF INTESTINAL PARASITIC INFECTIONS IN A VILLAGE, IN ISFAHAN AREA " - T. Jalayer; H. Farid; M. Shams (Tehran University of Medical Sciences, 1976)
Previous reports on intestinal parasite from Isfahan area revealed wide distribution of intestinal parasitic infections in the area. Since all studied areas were situated in the banks of Zayandeh rood river with lot of trees and a humid soil, it was suggested, for comparison, to undertake a similar study in a village with comparatively dry and district climate. The village Segzi (42 kilometer, east bf Isfahan city) was selected for the study. 416 stool samples were collected from 1,400 villagers and were examined by the following methods: 1) direct saline smear 2) direct iodide smear, 3) saturated salt flotation, and 4) hydrochloric acid-ether sedimentation: The results revealed that the four most prevalent helminthic infections, were Ascaris lumbricoides, Trichuris trichiura. Trichostronglylus spp. and Hymenolepis nana with 76.9.2, 69.95, 58.41 and 8.41 per cent, infection rates respectively. Entamoeba coli, Iodamoeba butschlii, Giardia intestinalis, Endolimax nana and Chilomastix mesnili with 26.92, 12.74, 9'86, 5.53 and 3.61 per cent, infection rates respectively, were the prevalent intestinal protozoan infections comparison of the figures reported in this study with previously reported ones from other temperate zones of the province shows that dry and desert climate, at least in Segzi village, had no effect, on the transmission of the above mentioned parasites.